Giving women WOICE postpartum: prevalence of maternal morbidity in high-risk pregnancies using the WHO-WOICE instrument - M. N. Lamus; S. Pabon; C. MPoca; J. P. Guida; M. A. Parpinelli; J. G. Cecatti; M. F. Vidarte; M. L. Costa (BMC, 2021)
Abstract Background There are no accurate estimates of the prevalence of non-severe maternal morbidities. Given the lack of instruments to fully assess these morbidities, the World Health Organization (WHO) developed an instrument called WOICE. We aimed to evaluate the prevalence of non-severe maternal morbidities in puerperal women and factors associated to impaired clinical, social and mental health conditions. Method A cross-sectional study with postpartum women at a high-risk outpatient clinic in southeast Brazil, from November 2017 to December 2018. The WOICE questionnaire included three sections: the first with maternal and obstetric history, sociodemographic data, risk and environment factors, violence and sexual health; the second considers functionality and disability, general symptoms and mental health; and the third includes data on physical and laboratory tests. Data collection was supported by Tablets with REDCAP software. Initially, a descriptive analysis was performed, with general prevalence of all variables contained in the WOICE, including scales on anxiety and depression (GAD-7 and PHQ-9- impaired if ≥10), functionality (WHODAS- high disability scores when ≥37.4) and data on violence and substance use. Subsequently, an evaluation of cases with positive findings was performed, with a Poisson regression to investigate factors associated to impaired non-clinical and clinical conditions. Results Five hundred seventeen women were included, majority (54.3%) multiparous, between 20 and 34 years (65.4%) and with a partner (75,6%). Over a quarter had (26.2%) preterm birth. Around a third (30.2%) reported health problems informed by the physician, although more than 80% considered having good or very good health. About 10% reported any substance use and 5.9% reported exposure to violence. Anxiety was identified in 19.8% of cases, depression in 36.9% and impaired functioning in 4.4% of women. Poisson regression identified that poor overall health rating was associated to increased anxiety/depression and impaired functioning. Having a partner reduced perception of women on the presence of clinical morbidities. Conclusion During postpartum care of a high-risk population, over one third of the considered women presented anxiety and depression; 10% reported substance use and around 6% exposure to violence. These aspects of women's health need further evaluation and specific interventions to improve quality of care.